Universal support for triangulated categories - Balmer, Paul; Sanchez Ocal, Pablo (Comptes Rendus. Mathématique)
We revisit a result of Gratz and Stevenson on the universal space that carries supports for objects of a triangulated category, in the absence of a tensor product.